2023
DOI: 10.1001/jamainternmed.2023.0325
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Medical Consultation With Reduction in Adverse Postoperative Outcomes and Use of Processes of Care Among Residents of Ontario, Canada

Abstract: ImportanceIt is uncertain whether preoperative medical consultation reduces adverse postoperative clinical outcomes.ObjectiveTo investigate the association of preoperative medical consultation with reduction in adverse postoperative outcomes and use of processes of care.Design, Setting, and ParticipantsThis was a retrospective cohort study using linked administrative databases from an independent research institute housing routinely collected health data for Ontario’s 14 million residents, including sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…To the Editor We congratulate Dr Beckerleg and colleagues on their exploration of this topic and their findings that raise questions regarding the relevance of perioperative medical consultation and its association with patient outcomes. The goal of perioperative consultation has been to reduce surgical morbidity and adverse events; however, its effects have been challenging to study in an organized manner.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor We congratulate Dr Beckerleg and colleagues on their exploration of this topic and their findings that raise questions regarding the relevance of perioperative medical consultation and its association with patient outcomes. The goal of perioperative consultation has been to reduce surgical morbidity and adverse events; however, its effects have been challenging to study in an organized manner.…”
mentioning
confidence: 99%
“…Although this article highlights the importance of studying the role and benefit of preoperative medical optimization, the conclusion that “preoperative medical consultation was not associated with a reduction but rather with an increase in adverse postoperative outcomes” is perhaps too definitive. A causal link is difficult to identify within the constraints of this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor Dr Beckerleg and colleagues observed that preoperative medical consultations were not associated with a reduction but rather with an increase in adverse postoperative outcomes . Unfortunately, from the article we learn little regarding the indications, quality, or results of these preoperative medical consultations.…”
mentioning
confidence: 99%
“…Regarding comments about patient selection and confounding, we agree and acknowledged in our study limitations that our conclusions do not apply to patients who may have had their surgical procedures canceled after preoperative medical consultations, and that the issue of potential residual confounding is inherent in observational designs. Whether through propensity score methods or regression-based adjustment, residual confounding is likely to remain.…”
mentioning
confidence: 99%